Pengaruh media audiovisual berbasis game education kahoot terhadap hasil belajar peserta didik kelas IV pada pembelajaran IPAS - Nabila Nur Fauzia; Rapani Rapani; Rabiyatul Adawiyah Siregar; Muhammad Nurwahidin (Universitas Sebelas Maret, 2025)
This study discusses the low learning outcomes of students in the subject of science in grade IV at Nurul Huda Islamic School Elementary School. The purpose of this study was to determine the effect of audiovisual media based on educational game kahoot on the learning outcomes of grade IV students in science learning. The data collection techniques used tests and non-tests. This study employed quantitative research with a Quasi Experiment Design and a Non-Equivalent Control Group Design type. The population consisted 90 students and the sample used was 60 students, the sample was determined using a random sampling technique. The data were analyzed using a simple linear regression test, which showed a significant effect of the use of audiovisual media based on educational game kahoot on the learning outcomes of grade IV students in science learning at Nurul Huda Islamic School Elementary School, indicated by the acquisition of a significance coefficient value of 0.000 <0.05. Based on these results, H0 is rejected and Ha is accepted, which means that there is an effect of the use of audiovisual media based on educational game kahoot on the learning outcomes of grade IV students in science learning at Nurul Huda Islamic School Elementary School.